Electrochemical response of several cathode configurations prepared with Ba0.5Sr0.5Co0.8Fe0.2O3-δ and Ce0.9Gd0.1O1.95 for IT-SOFC - Setevich, Cristian (2016)
The electrochemical response of Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) electrodes prepared by an acetic acid-based gel route has been investigated by impedance spectroscopy (IS) as a function of temperature (400 ≤ T ≤ 900 °C) and oxygen partial pressure (1 × 10−3 ≤ pO2 ≤ 1 atm). Several electrode configurations were studied using Ce0.9Gd0.1O1.95 (GDC) as the electrolyte. These consisted of one BSCF layer (cell A), a BSCF layer with an intermediate porous GDC layer (cell B), and graded electrodes using a composite BSCF+GDC, with variations in the surface area of GDC (cells C and D). The optimum heat treatment for the electrode assemblages was determined to be around 850–900 °C. Analysis of the impedance spectra shows that at T ≥ 600 °C a low frequency (LF) contribution, associated to the gas phase diffusion is systematically the rate-limiting step. All the electrodes show an intermediate frequency (IF) arc related to mixed processes. For cells A and B, the IF response is related to the oxide ion transfer at the electrode/electrolyte surface and the charge transfer at the electrode surface, while for cells C and D the mixed process involves the charge transfer and the molecular oxygen dissociation at the electrode surface.